(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The importance of drawing is among the most common discourses in architectural practice and education. Current research investigating the relation between drawing ability and architecture students’ study performance give various results, indicating that context plays significant role in determining such relationship. Therefore, using a quantitative manner using simple measurement of correlations, this study aims to add insights to this issue by exploring the connection between architectural students’ drawing ability and the results of stages of design studios wherein one studio emphasizes one facet of design at a time, within the context of undergraduate architecture education at Universitas Gadjah Mada, Yogyakarta, Indonesia. The results reveal that, although the correlations vary throughout phases of the studios, the importance of hand-drawing ability is more prominent at certain studio emphasizing the ability to orchestrate form-space and to present design products by hand-drawing, suggesting the noteworthy role of hand-drawing in both envision and presentation.